HUBUNGAN SELF-EFFICACY IBU DENGAN KEJADIAN STUNTING PADA ANAK BADUTA - Viska Ruth Dameria; Linda Sari Barus; Lidwina Triastuti Listianingsih (Journal of Innovation Research and Knowledge, 2025)
Main nutritional problem Indonesia currently facing is stunting. Preliminary study found 123 stunted children in Cimareme Health Center. Stunting is growth and development disorder due to chronic malnutrition. Mother’s self-efficacy in providing complementary food is mother's belief in child’s feeding. This study aims to determine relationship between mother’s self-efficacy and incidence of stunting. This study used quantitative method of correlation design with cross-sectional approach. Sample of 129 respondents taken by accidental sampling technique. Data collection tools used complementary feeding self-efficacy (CFSE) questionnaires and child height measurement. Data analysis using Chi-Square test. Results showed 69 respondents (53.5%) had high self-efficacy and 104 respondents (80.6%) had children who weren’t stunted. Chi-Square test found that there was a relationship between mother’s self-efficacy and incidence of stunting with p-value (0.000). Nutrition assistance is needed for mothers with low self-efficacy and who have stunted children in order to increase confidence in preparing complementary foods